Othmar Schoeck life and works - Walton, Chris 1963- (Boydell & Brewer, 2009)
In this, the first extended study of Schoeck in English, Walton places the man and the artist squarely in the context of his time. The work of the late-Romantic Swiss composer Othmar Schoeck (1886-1957) has in recent years enjoyed a surge of interest. His 300 songs with piano accompaniment are now all on CD, as are his orchestral song cycles and five of his eight stage works. Yet despite an impressive discography featuring names such as Dietrich Fischer-Dieskau, Lucia Popp and Ian Bostridge, no biographical study of Schoeck has ever been available in English. Chris Walton, author of Richard Wagner in Zurich: The Muse of Place, charts the turbulent course of Schoeck's life and career with care and candor, from a rampant youth to midlife monogamy and an old age ravaged by fears of neglect. He traces Schoeck's relationships to musicians such as Max Reger, Ferruccio Busoni, Wilhelm Furtwängler, Paul Hindemith, and Igor Stravinsky, and to writers Thomas Mann, Hermann Hesse, and James Joyce. New light is also shed on Schoeck's uneasy relationship with Nazi Germany and its culmination, for him, in public humiliation and private catastrophe. As an accompanist, Schoeck was an arch-Romantic master of 'rubato'; as a conductor, he was a fervent champion of the new; and in his compositions, he moved from late-Romanticism through a modernist vortex to emerge in full mastery of an individual musical language both sensuous and stringent. Chris Walton is Extraordinary Professor at the University of Stellenbosch in South Africa and managing director of the Orchestre Symphonique Bienne in Switzerland. He is the recipient of the 2010 Max Geilinger Prize honoring exemplary contributions to the literary and cultural relationship between Switzerland and the English-speaking world
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Schoeck, Othmar / 1886-1957; Schoeck, Othmar -- 1886-1957; Composers / Switzerland / Biography; Schweiz; Biografie